Morphological and physiological traits of the mesonephros in a freshwater fish, grayling Thymallus thymallus - E. A. Flerova; A. A. Morozov; A. A. Bogdanova; D. V. Chupov; G. M. Ustiuzhinskii; V. V. Yurchenko (Regulatory Mechanisms in Biosystems, 2019)
The study presents new data on the structural and functional organization of the mesonephros of the grayling Thymallus thymallus (Linnaeus, 1758). Adult grayling were sampled in the middle course of the Unya River, a tributary of the Pechora River (Komi Republic, Russia). The mesonephros of the grayling, as of other freshwater fishes, is composed by nephrons, blood vessels and hematopoietic tissue forming the renal interstice. In the interstice, сells with a radial vesicle array and chloride cells were discovered; the latter were mostly localized near the renal tubules. The degree of the interstice development in the mesonephros of the grayling was determined. New data on the ultrastructure of leukocytes, cells with a radial vesicle array, chloride cells, and nephron segments were obtained. A lack of mesangial cells, a small number of podocytes, and a thin basement membrane were observed on the sections of a renal corpuscle, being characteristic features of the ultrathin organization of the mesonephros in freshwater members of Salmoniformes and Esociformes. In the grayling’s nephrons, no neck segment was found, which was reported earlier for several species, including mammals. On the sections of proximal tubules, the ciliated cells were rare, and large amounts of the tubular-vesicular network in the zone of endocytosis of the type II epithelial cells were observed. On the sections of distal tubules, short blade-shaped cytoplasmic processes, with large numbers of invaginations of cytoplasmic membrane, were found. On the basis of the distinctive ultrastructure features mentioned above, the inference that grayling show the cytological markers of adaptation to euryhalinity was made. Thus, the results contribute to the knowledge of mesonephros development in fishes during their life history. From the species protection standpoint, our study provides baseline data on a WBC differential in the mesonephros as well as superoxide dismutase, catalase, glutathione S-transferase, and ethoxyresorufin-O-deethylase activities, which can be used in further studies addressing the health status of grayling populations.